Counseling and discipline practices of selected basic education institutions - Antonio, Gabbi C. (College of Education, University of the Philippines Diliman, 2018)
This study explored the counseling and discipline practices across basic education institutions. Using a qualitative research design, 30 teacher-advisers from private and public schools were involved the study and undergone a series of interviews. Results showed that the issues and concerns assessed are attributed to social and environmental factors.